THE IMPORTANCE OF LOGISTICS IN THE SPHERE OF TRANSPORTATION AND TOURIST SERVICES - Farmon, Asadov (Центр Научных Публикаций (buxdu.uz), 2022)
this article discusses the importance of logistics in the field of transport and tourism, its role in the development of these sectors, and also proves that logistics is one of the most important factors affecting the transport and tourism market. Given that the demand for travel and transport services continues to decline in the context of the pandemic, it was emphasized that attention needs to be paid to logistics to stem this decline.